Pelatihan Pembuatan Pestisida Nabati Sebagai Alternatif Pengendalian Serangga Hama Tanaman Pada Petani Sayur di Desa Bulotalangi Timur - Nurhayati Bialangi; Erni Mohamad; Mangara Sihaloho; Ahmad Kadir Kilo; Julhim S Tangio (Damhil: Jurnal Pengabdian kepada Masyarakat, 2023)
This service activity aims to provide training on making vegetable pesticides to farmers and housewives. As an alternative to controlling plant insect pests, the use of vegetable pesticides is considered safe to use. Botanical Pesticides are pesticides whose active ingredients come from plants or herbs and other organic materials which are efficacious in controlling pest attacks on plants. This pesticide does not leave harmful residues on plants or the environment and can be made easily using inexpensive materials and simple equipment. Vegetable pesticides are relatively easy to make with natural or vegetable ingredients which make these pesticides easy to decompose in nature so they don't pollute the environment. This organic pesticide is able to overcome and repel pests that destroy agricultural and plantation crops in general, such as fleas, caterpillars, grasshoppers and so on. The method used is direct training to groups of housewives and vegetable farmers using innovative technology. From the results of the implementation of these activities, the community was very enthusiastic about participating in these activities and was interested in making/producing their own pesticides from materials that are easy to obtain from the surrounding environment